Pure and Fresh: A Typology of Formal Garden Scenes from Private Eighteenth Dynasty Theban Tombs Prior to the Amarna Period - Reichart, Jayme Rudolf (AUC Knowledge Fountain, 2021)
Gardens in ancient Egypt are known from the Early Dynastic Period to the Graeco-Roman Period from archaeological, textual, and pictorial evidence. From this evidence, one can differentiate between simple and formal gardens. This thesis exclusively produces a typology of the S- and Domain of Amun formal garden scenes (the xnty-S-, kAmw-, sS-, at-nt-xt-, and Hrrt-S-formal gardens) represented in the early to mid-late Eighteenth Dynasty Theban private tomb art prior to the Amarna Period (TT E2, TT 39, TT 63, TT 80, TT 81, TT 85, TT 87, TT 90, TT 93, TT 96, TT 100, TT 109, TT 161, and TT 334) by their Egyptian names. These formal gardens are examined in this study through (i) visual analyses and (ii) discussions in terms of their additional extant evidence, tomb locations, flora and fauna they sustained (including their actual growth cycles, as well as use, symbolism, and significance for the ancient Egyptians in life and death found in Appendix II: Herbarium and Faunarium), and wider sociocultural significance and relevance to the tomb-owners’ titles in early to mid-late Eighteenth Dynasty Thebes prior to the reign of Amenhotep IV/Akhenaten. This study concludes that the formal gardens represented as tomb scenes, and the actual ones known from extant textual, pictorial, and/or archaeological evidence of the period, were symmetrical and even sometimes asymmetrical landscapes, that were located in proximity to either private homes and tombs, palatial residences, cult and/or memorial temples/shrines, and domains. The S-formal gardens were first constructed by the pharaohs, who sometimes gifted them to private and royal individuals, and which influenced other elite individuals, who had the power and resources, to construct ones of their own. The xnty-S-, kAmw-, sS-, at-nt-xt-, and Hrrt-S-formal gardens were principally constructed as monuments (mnw) by the kings for their palaces or for the gods. In the royal and private spheres, the S- and Domain of Amun formal gardens were aesthetic landscapes with numerous features used for sports, leisure, music, song, and dance performances, boat rites, meals, wakes, private banquets, and/or religious festivals and rituals, as well as provided surplus flower, herb, wine, fruit, fish, fowl, incense, and/or honey production for the institution(s) to which they were connected. Important to note is that the native and foreign flora of these formal gardens would have been purchased and/or introduced locally as seeds, fruit, and/or potted young specimens via gardeners or one’s other gardens or via foreign trade. Each of the 42 floral and 11 faunal species identified in these formal gardens have a specific growth and/or development cycle, which only allows them to be in bloom and/or available for harvest during a certain time of the year for use in food, medicine, festivities, meals, banquets, offerings, and floral arrangements, etc. Additionally, these formal gardens and their production were established, constructed, cultivated, maintained, overseen, and administered by intricate networks of individuals who worked in and/or liaised with them directly or indirectly. This relationship was evident in terms of the relevant titles of the tomb-owners and their colleagues, as well as from the location of the formal garden scenes in the porticos, transverse halls, passages, and chapels of the tombs in proximity to other self-glorifying ‘focal representations’ (Blickpunktsbilder) that would have been regularly viewed by family and community members and ideally visited by the bA and kA of the tomb-owner after death.